Robotic Milking Systems: A Review - Amer N. N. Kakahy; Rawezh D. Sidiq; Naz M. Ghazi; Omar H. Mohammad; Heba Mohammed Alhamdany (American Journal of Botany and Bioengineering, 2026)
In dairy farming, robotic milking systems (RMS) replace manual labor with automatized, data-driven methods. This review focuses on the technological advancement, benefits, challenges, and future development of RMS in relation to milk production, animal welfare, and farm efficiency. RMS enables precision livestock management by integrating sensors, AI, and real-time analytics. This enables proactive health tracking and tailored cow management. The improved milk quality, more frequent milking, and lower labor costs are among the main advantages. Machine learning and system integration are needed to maximize sustainability and scalability. However, there are barriers to adoption, such as a high initial investment cost, technical complexity, and the need for skilled maintenance. RMS is ready to revolutionize how milk is produced as the dairy industry embraces Industry 4.0 by balancing environmental and ethical concerns with productivity.